PROBLEMATYKA PRACY W POLSCE W LATACH 90-TYCH - Suwalski, Andrzej (Wydział Prawa i Administracji UAM, 2000)
The some issues connected with the problems of labour market in the nineties are discussed in the article. The analysis focuses on the substance of employment guarantees, determination of labour conditions, earnings sphere as well as employees’ participation.
SOME CONTROVERSIAL ISSUES OF LABOUR PROBLEMS IN POLAND IN THE NINETIES